Die Vorläufigkeit von »Menschenpflichten« für den buddhistischen Erlösungsweg: religionswissenschaftliche Gesichtspunkte zur heutigen Diskussion über universelle Menschenpflichten - Hutter, Manfred (Zeitschrift für evangelische Ethik, 2000)
The »Universal Declaration of Human Responsibilities«, published by the InterAction Council in 1997, aims to foster human and ethical development in a global society. The purpose of this paper is to ask in which way it is possible to accept this declaration within the context of a specific religion - e.g. Buddhism. From the point of view of Buddhist ethics it is worthy to mention that the fulfillment of human responsibilities cannot be the main topic for ethical behaviour because it only leads to further attachement within the material world and not to nirvana (salvation). Living as a Buddhist leads to ethical behaviour but doing all one's responsibilities is only a preliminary task.